The curse of the golden heart - Suzanne, Jamie; Pascal, Francine; Copyright Paperback Collection (Library of Congress) (New York : Bantam Books, 1994)
It's spring break, and the twins are taking a scuba diving course at Pirates Cove. On their first dive the twins discover the remains of an old pirate ship, and half a golden heart buried in the sand. Can Elizabeth discover the secret of the golden heart before the curse destroys her?
"A Bantam Skylark book."
On cover: Francine Pascal's Sweet Valley twins and friends.
.
Keywords: Twins -- Juvenile fiction; Children's stories; Mystery fiction